Phonetic changes in the Latin of Noricum - Gonda, Attila (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Previous studies analyzed the Vulgar Latin of the inscriptions of Pannonia Inferior, Dalmatia and Venetia et Histria, comparing the differences between the provincial capitals and the countryside of the provinces, in order to verify the hypothesis of Untermann (1980) and Herman (1983) about the existence of a larger regional dialect of Latin over the Alps–Danube–Adria region. The analyses made clear that these geographic unites don’t constitute a solid and uniform dialectal area, but there are undeniable common characteristics, such as the weakness of the /w/~/b/ merger or the lack of sonorization, which allow us to suppose that the Vulgar Latin variants of these provinces were somewhat more connected among each other than with the rest of the empire. This study involves another province of the Alps–Danube–Adria region, Noricum, in the examination, systematically discusses the changes in the vowel and consonant systems based on the relative distribution of diverse types of non-standard data from the inscriptions of Noricum, and contrasts the linguistic phenomena of an earlier period (1st–3rd c. AD) with a later stage (4th–6th c. AD) of Vulgar Latin, attempting to define whether Noricum fits common characteristics found in the other provinces of the Alps–Danube–Adria region.